2016
DOI: 10.1177/1474515116643622
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare needs of adolescents with congenital heart disease transitioning into adulthood: a Delphi survey of patients, parents, and healthcare providers

Abstract: Background: The increasing survival of children with congenital heart disease (CHD) challenges healthcare systems regarding how to manage the many health needs of patients undergoing transitional care. A comprehensive understanding of the perspectives of patients, parents, and healthcare providers is required. Objective: This study systematically identified the healthcare needs of adolescents with CHD transitioning into young adults by collecting the perspectives of patients, parents, and healthcare providers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
(53 reference statements)
0
39
0
Order By: Relevance
“…The Healthcare Needs Scale for Youth with CHD (HNS‐CHD) used in this study originated from the findings of the authors’ previous Delphi study regarding the healthcare needs of adolescents with CHD during transition to adulthood (Chen et al., ). The face and content validity of HNS‐CHD has been established by a consensus on 25 healthcare needs reached by youth with CHD, parents and healthcare providers.…”
Section: The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The Healthcare Needs Scale for Youth with CHD (HNS‐CHD) used in this study originated from the findings of the authors’ previous Delphi study regarding the healthcare needs of adolescents with CHD during transition to adulthood (Chen et al., ). The face and content validity of HNS‐CHD has been established by a consensus on 25 healthcare needs reached by youth with CHD, parents and healthcare providers.…”
Section: The Studymentioning
confidence: 99%
“…In the present study, the HNS‐CHD consisted of 25 items regarding the importance level of needs perceived by the participants rated on a 5‐point Likert scale, ranging from 1 (very unimportant)—5 (very important). The HNS‐CHD measured five domains of healthcare needs that youth with CHD may identify: health, family, individual, interpersonal and policy needs (Chen et al., ). A high score indicated that a need was crucial, whereas a low score indicated a less important need.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Arch Nurs Pract Care 3(2): 031-037. DOI: http://dx.doi.org/10.17352/anpc.000022 from childhood to adulthood in patients with CHD, in order to develop the purposeful transition care models, which are aimed to provide self-management and to satisfy the medical, psychosocial, educational, and employment needs of CHD adolescents [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…With a prevalence of 9.1 for 1000 live births [1], the CHD are the leading causes of birth defectsassociated morbidity, mortality, and medical expenditures [2].…”
Section: Introductionmentioning
confidence: 99%